Strategi Peningkatan Mutu Manajemen Pelayanan Bus Sekolah Gratis Di Wilayah Kabupaten Lampung Selatan - Arif Kurniawan; Saptarini Saptarini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The Public School Bus Service in South Lampung Regency is a form of public transportation service provided by the local government to support students’ safety and mobility in accessing educational activities. This service is implemented by the Department of Transportation as part of public service delivery in the transportation sector and is provided free of charge. However, in its implementation, various issues remain that have resulted in suboptimal service quality and a declining level of public interest in utilizing the service. This study aims to analyze the factors that hinder the quality of the Public School Bus Service in South Lampung Regency and to formulate strategies for improving service quality that can be implemented by the local Department of Transportation. This research employs a qualitative approach, with data collected through interviews, observations, questionnaires, and documentation. Data analysis was conducted using a Fishbone (Ishikawa) diagram with a 5M approach to identify the root causes of service-related problems, which were subsequently analyzed using SWOT analysis as the basis for formulating service quality improvement strategies. The findings indicate that the quality of the Public School Bus Service is influenced by limitations in operational management, inadequate route coverage that has not yet reached all schools, constraints in human resources and supporting facilities, and the absence of optimal evaluation and service quality monitoring mechanisms. These constraints have contributed to the low utilization of the Public School Bus Service by the community. Based on the SWOT analysis, several service improvement strategies were formulated, focusing on strengthening service management, enhancing quality management practices, improving human resource capacity, and reinforcing coordination with relevant stakeholders. The study concludes that improving the quality of the Public School Bus Service requires integrated and sustainable service management in order to meet community needs and support effective public service delivery in South Lampung Regency.